2015
DOI: 10.17795/zjrms1275
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alcoholic Extract of Persian Gulf Chiton (lamyi) Shell on Angiogenesis in Chick Chorioallantoic Membrane

Abstract: Background: Inhibition of angiogenesis is a major target in control and treatment of many disorders depend of angiogenesis. Chiton is a marine mollusk and it can be useful for treatment of diseases because of exist many chemical compositions in its. We investigated the effects of shell extract of chiton on angiogenesis in chorioallantoic membrane. Materials and Methods:In this experimental study, we used 30 Ross fertilized eggs that were divided into 3 random groups: control, sham-exposed (treated by dimethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Molluscs are known for their bioactive compounds and have become a focus of many studies aimed at discovering and isolating novel natural products [ 19 ]. In a recent study, Bojnourdi et al [ 20 ] investigated the anti-angiogenic properties of shell extract of the mollusc chiton on CAM model and found that it produced maximum 58% anti-angiogenic activity. In another interesting study by Gupta et al [ 21 ], 22 different marine invertebrate extracts were screened for their anti-angiogenic activity, out of which, Meretrix meretrix (47.01% inhibition), Meretrix casta (64.63% inhibition), Telescopium telescopium (62.02% inhibition) and Bursa crumena (60.48% inhibition) showed significant anti-angiogenic activity in CAM.…”
Section: Discussionmentioning
confidence: 99%
“…Molluscs are known for their bioactive compounds and have become a focus of many studies aimed at discovering and isolating novel natural products [ 19 ]. In a recent study, Bojnourdi et al [ 20 ] investigated the anti-angiogenic properties of shell extract of the mollusc chiton on CAM model and found that it produced maximum 58% anti-angiogenic activity. In another interesting study by Gupta et al [ 21 ], 22 different marine invertebrate extracts were screened for their anti-angiogenic activity, out of which, Meretrix meretrix (47.01% inhibition), Meretrix casta (64.63% inhibition), Telescopium telescopium (62.02% inhibition) and Bursa crumena (60.48% inhibition) showed significant anti-angiogenic activity in CAM.…”
Section: Discussionmentioning
confidence: 99%